An index of coastal thermal effects of El Niño Southern Oscillation on the Peruvian Upwelling Ecosystem. (23rd April 2018) - Quispe‐Ccalluari, C.; Tam, J.; Demarcq, H.; Chamorro, A.; Espinoza‐Morriberón, D.; Romero, C.; Dominguez, N.; Ramos, J.; Oliveros‐Ramos, R.
Abstract : A Peruvian Coastal Thermal Index (PCTI) was developed from 1982 to 2014 for the detection and forecasting of warm and cold periods off Peru. It showed differences in thermal conditions between the Peruvian Upwelling Ecosystem (PUE) and the Equatorial Pacific Ocean usually monitored by the Oceanic Niño Index (ONI). This index represented 87.7% of the total variation of the sea surface temperature anomalies on the PUE. Abstract : The Peruvian Upwelling Ecosystem (PUE) is one of the most productive ecosystem in the world in terms of productivity and fish catches, partly because its geographical location is affected by remote physical processes, such as the interannual climate variability of the Equatorial Pacific Ocean (EPO), whose dominant signal is El Niño Southern Oscillation (ENSO). In order to assess the thermal effects of ENSO off Peru, a Peruvian Coastal Thermal Index (PCTI) was developed representing 87.7% of the total variation of the Sea Surface Temperature (SST) anomalies of the PUE. Between 1982 and 2014, the PCTI detected 12 warm periods and 16 cold periods in the PUE. PCTI had a linear trend component, a low frequency component and a noise component, with 1.5%, 94.5% and 4% contributions to the total variance, respectively. Wavelet analysis of PCTI showed significant peaks of variability between the years 1996 and 1999 between periods of 0.4 and 6 years. A regime shift in variance of PCTI was detected in 1999, with a lower variance between 1999 and 2014 than between 1982 and 1998, which agreed with the start of a cold phase of the Pacific Decadal Oscillation. The decrease of variance of the PCTI could be linked to an increase of the local winds associated with a higher intensity of the average state of South Pacific Anticyclone. This atmospheric change might have strengthened the coastal upwelling and counteracted the intensity of warm periods in the PUE. Finally, the comparison of different indexes allowed to detect four periods where neutral conditions occurred in the EPO while warm periods occurred in the PUE (1993, 2008, 2012 and 2014); and 1 period where a warm episode occurred in the EPO (2004–2005) while a neutral condition occurred in the PUE.